2009
DOI: 10.1016/j.bbamcr.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular basis of lysosomal transmembrane protein dysfunction

Abstract: Lysosomal membrane proteins act at several crucial steps of the lysosome life cycle, including lumen acidification, metabolite export, molecular motor recruitment and fusion with other organelles. This review summarizes the molecular mechanisms of lysosomal storage diseases caused by defective transport of small molecules or ions across the lysosomal membrane, as well as Danon disease. In cystinosis and free sialic acid storage diseases, transporters for cystine and acidic monosaccharides, respectively, are bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 166 publications
0
68
0
Order By: Relevance
“…Its mechanisms in lysosomal storage disorders, however, are not well understood. Some of the current models, including suppressed flow of key substrates or accumulation of effete organelles due to autophagy block, have been discussed (25,59,60). Here we show that in addition to the "supply side" issues in lysosomal storage diseases, an active and early CatB release mechanism specifically caused by TRPML1 loss takes place soon after TRPML1 KD.…”
Section: Discussionmentioning
confidence: 80%
“…Its mechanisms in lysosomal storage disorders, however, are not well understood. Some of the current models, including suppressed flow of key substrates or accumulation of effete organelles due to autophagy block, have been discussed (25,59,60). Here we show that in addition to the "supply side" issues in lysosomal storage diseases, an active and early CatB release mechanism specifically caused by TRPML1 loss takes place soon after TRPML1 KD.…”
Section: Discussionmentioning
confidence: 80%
“…Consistent with this postulation, overexpression of ATP13A2 resulted in a reduced intracellular Mn 2ϩ concentration. Moreover, neurodegeneration with brain iron accumulation and other neuronal system diseases are caused by defects in lysosomal membrane proteins (37,38). Even though no specific substrate of ATP13A2 has been identified, brain MRIs indicate that patients with ATP13A2 mutations show generalized atrophy of the putaminal and caudate with bilateral iron accumulation (2,9).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Autophagosomes fuse with lysosomes to form autolysosomes, mediated by a receptor in the lysosomal membrane -the lysosome-associated membrane protein 2 (Lamp-2). 10 In the autolysosomes, the luminal cargo is degraded by lysosomal enzymes. 6,7,10 Some studies have shown that activation of autophagic flux plays a crucial role in a variety of conditions, including tumor suppression, immune A previous study from our laboratory showed melatonin protects neuronal cells against prion protein (PrP) (106-126)-mediated mitochondrial neurotoxicity via upregulation of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…10 In the autolysosomes, the luminal cargo is degraded by lysosomal enzymes. 6,7,10 Some studies have shown that activation of autophagic flux plays a crucial role in a variety of conditions, including tumor suppression, immune A previous study from our laboratory showed melatonin protects neuronal cells against prion protein (PrP) (106-126)-mediated mitochondrial neurotoxicity via upregulation of autophagy. 12 Moreover, GO can simultaneously trigger an antitumor effect and activate an immune response through activation of autophagic flux.…”
Section: Introductionmentioning
confidence: 99%